Rapid detection of high consequence and emerging viral pathogens in pigs - Neujahr, Alison C.; Loy, Duan S.; Loy, John Dustin; Brodersen, Bruce W.; Fernando, Samodha C. (Frontiers in Veterinary Science, 2024)
An increasing emergence of novel animal pathogens has been observed over the last decade. Viruses are a major contributor to the increased emergence and therefore, veterinary surveillance and testing procedures are greatly needed to rapidly and accurately detect high consequence animal diseases such as Foot and Mouth Disease, Highly Pathogenic Avian Influenza, Classical Swine Fever and African Swine Fever. The major detection methods for such diseases include real-time PCR assays and pathogen specific antibodies among others. However, due to genetic drift or shift in virus genomes, failure to detect such pathogens is a risk with devastating consequences. Additionally, emergence of novel pathogens with no prior knowledge requires non-biased detection methods for discovery. In this study, we developed a rapid, highly reproducible sequence-based approach to identify potential high consequence and novel pathogens in swine from complex clinical samples. This approach allows identification of both DNA and RNA viruses and bacterial pathogens simultaneously from a single tissue sample and provides results in less than 12 h. Preliminary evaluation of this method using surrogate viruses in different matrices and clinical samples from animals with unknown disease causality suggests that this method can be used to simultaneously detect multiple viruses from different tissue types rapidly and with high confidence.